(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The paper presents a very relevant problem in educational practice – how to develop interest in a difficult physics course and its successful understanding. The principles of developmental education, the activity approach, problem solving-based education, high motivation, compulsory success.